Behaviour of trinitrotoluene in electrokinetic soil processing - M. Raihan Taha,; Yalcin B. Acar,; Gale, Robert J.; Zappi, Mark E. (1998)
The behaviour and removal of trinitrotoluene (TNT) in contaminated soil under electrokinetic processes was investigated. The soil used in this study was obtained from the Hastings East Industrial Park site in Nebraska, USA. A current density of 123.3 μA/cm2 was applied to soil specimens compacted in glass cells. Test with water and a surfactant solution, SDS, as anolytes indicated that TNT concentrations in the soil sample decreased significantly at the sections closest to the cathode. This, however, was not due to removal of TNT away from the cathode. Extensive analysis indicated that the disappearance of TNT was possibly due to the transformation of TNT to TNT anions possibly due to reaction of TNT with base and reductive environment generated during electrolysis. These anions were not detected in initial analysis with high performance liquid chromatography using EPA method. The electrokinetic processes needs further engineering in order to enhance removal of TNT from soils